Diagnosis and treatment of ASD in women in secure and forensic hospitals. Issue 1 (12th March 2019) - Markham, Sarah
Abstract : Purpose: The purpose of this paper is to explore the experience and possibilities for misdiagnosis of women with ASD in secure and forensic hospitals, via the medium of a lived experience case study. To consider the clinical value of the patient perspective of and insight into their disorder. The case study is supplemented by relevant associations to the MHA Code of Practice, the CQC report, Monitoring the Mental Health Act (MHA) 2016–2017, published on 27 February 2018 and current research findings in the fields of service provision, quality of care and treatment of female patients with a diagnosis of ASD. Design/methodology/approach: A review and commentary of the author's lived experience of a formal diagnostic assessment for ASD as a female patient in a secure and forensic hospital. In reviewing aspects of the author's clinical assessment, the author has made contextual reference to the MHA Code of Practice, the CQC report, Monitoring the MHA 2016–2017, published on 27 February 2018, and current research findings. The account focuses on aspects of the author's recent experience assessment and treatment for ASD which the author believes may be of use in informing clinical practice. Findings: Open-ended exploration of a lived experience account/case study of a diagnostic assessment of an adult female patient for ASD, demonstrating the possible ambiguity of responses to questionnaire-based assessment tools and other deficiencies inherent to the assessment process and care and treatment of adult female ASD sufferers in secure and forensic hospitals. Research limitations/implications: The author uses the lived experience as a patient to review and provide commentary on the clinical assessment for ASD. This review is, therefore, informed by an authentic patient perspective and not clinical perspectives. This paper highlights the need for further research into the diagnostic assessment of females for ASD in a secure and forensic hospitals. Practical implications: First, to encourage practitioners to extend their range of thinking to be more inclusive of the patient perspective when performing a diagnostic assessment. Second, to increase practitioner awareness of the deficiencies in the current service provision for adult female patients diagnosed with ASD in secure and forensic hospitals. Social implications: To improve patient experience of diagnostic assessment for ASD and the quality of the assessment and patient outcomes in secure and forensic hospitals. Originality/value: The paper is original in concept in that it considers the inclusion of patient experience/views in assessment and formulation and links them to wider social policy and practice guidance. The case study is an authentic patient account informed by the author's experience of secure and forensic psychiatric hospitals. The value of the paper may be determined by the extent to which the paper encourages practitioners to consider the patient perspective and experience of the diagnostic assessment and how this and subsequent care and treatment may affect the adult female patient in secure and forensic hospitals.